"La palma entre las golosinas". Usos y significados del choique entre los indígenas pampeanos, siglo XIX. - Sánchez Azcárate, Felicitas (Memoria Americana, 2025)
In this work, we analyze the role of the choique (greater rhea) within the subsistence strategies of the Pampean indigenous groups during the second half of the 19th century. We studied those productive activities specific to the indigenous dynamic that persisted, with changes and continuities, until the last decade of existence of the southern border. The choique, a native species, was a key resource in these economies, not only for its nutritional value but also for its symbolic importance and its role in exchange networks. The study focuses on the salinero groups, led by Juan Calfucurá, who inhabited the Salinas Grandes and surrounding areas between the 1840s and 1870s. Through an analysis of historical, archaeological, and ethnohistorical sources, we reconstructed the choique hunting practices, the collective logics underlying these activities and their relationship to the construction of an indigenous territoriality.